Pengaruh Promosi dan Inovasi Produk terhadap Keputusan Pembelian Produk Al Futuh Fashion di Tasikmalaya - Pipit Dara Trisna (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect of simultaneous and partial promotion and product innovation on purchasing decisions on Al Futuh Fashion kawalu products in the city of Tasikmalaya. The research method used in this study is a quantitative approach with survey methods. The population in this study amounted to 105 respondents. The type of data used in this study is primary data obtained through questionnaire data. The data analysis used is the classical assumption test and multiple regression analysis using SPSS version 25. The results of this study indicate that promotion and product innovation simultaneously have a significant effect on purchasing decisions for al futuh Fashion kawalu products in the city of Tasikmalaya. Promotion, partially has a significant effect on product purchase decisions at the Al Futuh Fashion store. Product innovation partially has a significant effect on product purchasing decisions at the Al Futuh Fashion store in Tasikmalaya city